A Comparison between the Product-Refill and the Equalization Oxygen Pressure Swing Adsorption Processes - Abdel-Rahman, Zaid Adnan (Iraqi Journal of Chemical and Petroleum Engineering, 2018)
This work presents a design for a pressure swing adsorption process (PSA) to separate oxygen from air with approximately 95% purity, suitable for different numbers of columns and arrangements. The product refill PSA process was found to perform 33% better (weight of zeolite required or productivity) than the pressure equalization process. The design is based on the adsorption equilibrium of a binary mixture of O2 and N2 for two of the most commonly used adsorbents, 5A & 13X, and extension from a single column approach. Zeolite 13X was found to perform 6% better than zeolite 5A. The most effective variables were determined to be the adsorption step time and the operational pressure. Increasing the adsorption step time from 1 to 5 minutes decreased the performance by approximately 5 times. Increasing the pressure from 2 to 6 bars increased the performance by approximately 3 times.